Postoperative Intimal Hyperplasia: Review from My Research - Yamamura, Mitsuhiro (International Journal of Angiology, 2024)
Postoperative intimal hyperplasia is the major cause of the vein graft occlusion. It is very important to establish an animal model for the start of research. After my vascular surgery residency in Japan, I started my research work on postoperative intimal hyperplasia at the University of Wisconsin-Madison. My research showed that endothelial injury and monocyte infiltration is the key for postoperative intimal hyperplasia, which is very similar to Ross' pathogenesis of atherosclerosis as an inflammatory disease. Focusing on postoperative intimal hyperplasia as an inflammatory disease, especially on tumor necrosis factor-α, FR-167653 (tumor necrosis factor-α suppressive agent, inhibitor of p38 mitogen-activated protein kinase; Fujisawa Pharmaceutical Co., Ltd., Japan) is found to suppress postoperative intimal hyperplasia in a rat model by reducing serum monocyte chemoattractant protein-1 levels. However, FR-167653 is not commercially available today. Because endothelial injury is the first step of postoperative intimal hyperplasia, I investigated whether the free radical scavenger, edaravone (Radicut, Mitsubishi Tanabe Pharma Co., Japan), which alleviates the endothelial injury in vitro, can also suppress postoperative intimal hyperplasia. Moreover, the free radical scavenger edaravone (Radicut®, Mitsubishi Tanabe Pharma Co.) is also found to suppress postoperative intimal hyperplasia, by alleviating endothelial injury. In clinical settings, it is very important to detect postoperative intimal hyperplasia before its establishment. Hepatocyte growth factor is not only a hepatic growth factor but also a vascular endothelial growth factor. Recently, serum hepatocyte growth factor level was found to be a candidate biomarker for postoperative intimal hyperplasia in our rat model.
Keywords: postoperative intimal hyperplasia; endothelial injury; monocyte infiltration; monocyte chemoattractant protein-1; tumor necrosis factor-α suppressive agent; free radical scavenger; hepatocyte growth factor